Rethinking Global Economic Systems: A Unified Framework of Inequality, Sustainability, and Institutional Evolution - Raden Rudi Alhempi; Supaphorn Akkapin (Lafadz Jaya Publisher, 2025)
This study develops a unified conceptual framework to rethink global economic systems by integrating three critical dimensions: inequality, sustainability, and institutional evolution. Existing economic paradigms have largely treated these dimensions in isolation, resulting in fragmented policy approaches and limited explanatory power in addressing contemporary global challenges. This paper argues that the persistent rise in inequality, coupled with environmental degradation and institutional inefficiencies, reflects a systemic imbalance embedded within the current global economic architecture. Drawing on interdisciplinary insights from economics, institutional theory, and sustainability studies, this research adopts a qualitative conceptual approach to synthesize existing theoretical perspectives. The proposed framework conceptualizes global economic systems as dynamic and co-evolving structures in which distributional outcomes, environmental constraints, and institutional arrangements are interdependent. The analysis highlights how unequal resource allocation undermines sustainability goals, while weak institutional evolution constrains inclusive economic transformation. The study contributes to the literature by offering a holistic and integrative model that bridges the gap between growth-oriented and sustainability-oriented paradigms. It further provides a foundation for rethinking policy design by emphasizing the need for systemic alignment across economic, environmental, and institutional dimensions. The findings suggest that achieving long-term global stability requires a transition toward inclusive, adaptive, and sustainability-driven economic systems..